Women’s Language Features Used by Female Main Character in Superhero Movie - Ridho Saputra; Nyoman Udayana, I; Nyoman Sedeng, I (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study focused on analyzing women’s linguistic features used by the female main character in “Captain Marvel” movie. The theory used in this study is proposed by Lakoff, in which there are ten linguistic features of women’s speech. The data were collected by using observation and documentation methods. The descriptive qualitative approach is used to interpret the data and describe it in the form of words and sentences. The findings indicated that there were eight women linguistic features used by Carol Danvers as the female main character in the movie, such as rising intonation (10), lexical hedges or fillers (9), hypercorrect grammar (9), emphatic stress (7), tag questions (5), intensifiers (2), empty adjectives (1), and superpolite forms (1). Meanwhile, precise color terms and avoidance of strong swear words were not found in the utterances. The finding shows that the most dominant feature was rising intonations, while the least frequently emerged features were super polite forms and empty adjectives. The dominant use of rising intonation in the movie reflects the character’s personality. Therefore, it can be concluded that Carol Danvers used rising intonation because she is a bold character who is assertive, especially when stating her opinion